Analysis of step-velocity-dependent concentration of magnesium in GaN based on Burton−Cabrera−Frank theory and step-edge segregation model. (2nd December 2021) - Mochizuki, Kazuhiro; Kaneda, Naoki; Hayashi, Kentaro; Ohta, Hiroshi; Horikiri, Fumimasa; Mishima, Tomoyoshi
Abstract: Based on Burton−Cabrera−Frank theory and the step-edge segregation model, we analyzed the reported difference in the sheet concentration of doped magnesium under naturally formed surface stripes on homo-epitaxially grown layers on a freestanding GaN substrate misoriented from a c -plane by 0.3°. By assuming the step height being equal to the peak-to-valley height of the surface stripes, we considered the growth steps on gently and sharply sloped surfaces to be supplied, respectively, from mixed dislocations and the misorientation from the c -plane. The step-velocity dependence of the magnesium concentration was reproduced with the reported magnesium diffusivity of 3 × 10 −14 cm 2 s −1 .